2002
DOI: 10.1021/ic025734m
|View full text |Cite
|
Sign up to set email alerts
|

Forty-Five Years of Chemical Discovery Including a Golden Quarter-Century

Abstract: Inorganic chemistry became a passion for me as a graduate student in the 1950s. It was exciting to be part of the renaissance of the discipline, and I am pleased to have contributed to its strength. Physical concepts applied to the understanding of the properties of transition metal compounds guided our work initially. In the 1970s, probably as a direct result of the world abandoning the gold standard, the chemistry of gold was awakened after a long sleep. Much of the chemistry covered in this review of our wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 105 publications
2
134
0
1
Order By: Relevance
“…In general, two-coordinate gold(I) compounds experience attractive aurophilic interactions if the AuÀAu separations are below 3.6 ; their strength can be up to 10 kcal mol À1 for a dimeric unit, similar to standard hydrogen bonds. [24] The energetic contribution of longer Au À Au contacts is negligible.…”
Section: A C H T U N G T R E N N U N G {C 5 H 4 a C H T U N G T R E Nmentioning
confidence: 99%
“…In general, two-coordinate gold(I) compounds experience attractive aurophilic interactions if the AuÀAu separations are below 3.6 ; their strength can be up to 10 kcal mol À1 for a dimeric unit, similar to standard hydrogen bonds. [24] The energetic contribution of longer Au À Au contacts is negligible.…”
Section: A C H T U N G T R E N N U N G {C 5 H 4 a C H T U N G T R E Nmentioning
confidence: 99%
“…The results indicate that aurophilic bonding has a positive influence on the reaction rate but none on the distal size selectivity. Since previous kinetic studies have demonstrated that the rate-determining step of the gold-catalysed homocoupling of alkynes in solution is the oxidation of gold(I) 17 , it is not surprising that aurophilic bonding improves the reaction rate by neighbouring gold atomassisted oxidation of gold(I) 26,27 . To test if aurophilic bonding has also any influence in the distal size selectivity, we prepared the digold acetylide complexes 6a [Au 2 dppe(C 10 ) 2 ] and 6b [Au 2 dppe(C 12 ) 2 ], and the results after oxidation with selectfluor were compared with those obtained before for the corresponding monogold acetylides 3a-b.…”
Section: Resultsmentioning
confidence: 99%
“…Cocaine, heroin, morphine, and codeine are identified by microcrystal test with H [AuCl 4 ]. This test involves the addition of a 5% w/v solution of chloroauric acid in water (HAuCl 4 •3H 2 O) to a dilute aqueous acidified solution of suspected cocaine, followed by the observation of the resulting crystals microscopically of the envisaged salt (L-cocaine) [AuCl 4 ] as shown by X-ray crystallography [20,21].…”
Section: Microcrystal Test Using Goldmentioning
confidence: 99%
“…The degradation product L-ecgonine has been used as a marker for recent cocaine use [27]. The structure of the hydrated gold(III) tetrachloride salt of Lecgonine, (L-ecgonine) 4 − anions. For charge balance, one of the seven water molecules has to be a hydronium ion or one of the hydroxyl groups of the cations has to be diprotonated [20,21].…”
Section: Structure Of Gold Cocainementioning
confidence: 99%
See 1 more Smart Citation